The Efficiency of Educational Production: A Comparison of the Nordic Countries with other OECD Countries - Peter Bogetoft; Eskil Heinesen; Torben Tranaes (Center for Economic Studies and ifo Institute (CESifo), 2015)
Focusing in particular on upper secondary education, this paper examines whether the relatively high level of expenditure on education in the Nordic countries is matched by high output from the educational sector, both in terms of student enrolment and indicators of output quality in the form of graduation/completion rates and expected earnings after completed education. We use Data Envelopment Analysis (DEA) to compare (benchmark) the Nordic countries with a relevant group of rich OECD countries and calculate input efficiency scores for each country. We estimate a wide range of specifications in order to analyse different aspects of efficiency. In purely quantitative models (where inputs and outputs are expenditure and number of students at different levels of the educational system) and in models where graduation or completion rates are included as an indicator of output quality, Finland is the most efficient Nordic country (often fully efficient), whereas Sweden and especially Norway and Denmark are clearly inefficient. However, using PISA test scores as indicators of student input quality in upper secondary education reduces the inefficiencies of these three countries. Also, when expected earnings after completed education are used as an indicator of output quality, all Nordic countries are estimated to be fully efficient (or nearly so).
Keywords: C14; C61; H52; I21; I28; 330; Data Envelopment Analysis; benchmarking; upper secondary education; international comparisons